Sarcoidosis of the Bile Duct. Issue 1 (1st January 2023) - Alsayid, Muhammad; Taftaf, Ahmad; Harmouch, Khaled M.; Alabkaa, Anas; Pappas, Sam G.; Singh, Ajaypal
ABSTRACT: Sarcoidosis is an inflammatory disease that affects multiple organs. The lungs are the most commonly involved organs. Although a large proportion of patients with sarcoidosis have liver involvement, bile duct involvement is rare. Here, we present a case of a 56-year-old African American patient presented with painless jaundice because of extrahepatic bile duct sarcoidosis. Our diagnostic approach using endoscopic cholangioscopy with targeted biopsies confirmed the diagnosis. Multiple bile duct stent exchanges were performed to manage the bile duct stricture in addition to medical therapy.